1966
DOI: 10.1021/ic50046a025
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction Studies of Some Transition Metal Hexafluorides

Abstract: Crystallographic studies are presented for the transition metal hexafluorides MoFs, TcFB, RuFs, RhFs, WFs, ReFe, OsF6, IrFG, and PtF6. Each exhibits a cubic modification near room temperature and a phase of lower symmetry, probably orthorhombic, a t reduced temperatures.XRay results are presented for ReF7, which also exhibits a cubic phase a t room temperature and a second modification a t a very low temperature.Unit cell sizes for both phases as well as transition temperatures are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
2

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 12 publications
2
32
1
2
Order By: Relevance
“…The M3M' alloys with rare earths M' randomly distributed in 4(a)O h show the pedigree as shown in Table 5 (Siegel & Northrop, 1966) as the C2X 6 compounds with X = H, F, C1, Br and Me and C2H 4 and (CH2CN) z do (van Nes & Vos, 1978).…”
Section: The Fm3m Structure With 4(a)o Hmentioning
confidence: 99%
“…The M3M' alloys with rare earths M' randomly distributed in 4(a)O h show the pedigree as shown in Table 5 (Siegel & Northrop, 1966) as the C2X 6 compounds with X = H, F, C1, Br and Me and C2H 4 and (CH2CN) z do (van Nes & Vos, 1978).…”
Section: The Fm3m Structure With 4(a)o Hmentioning
confidence: 99%
“…Siegel & Northrop (1966) obtained X-ray powder photographs of the low-and high-temperature phases of all the above hexafluorides, and observed a similarity between the X-ray powder patterns of the low-temperature phases and that of UF6. The X-ray patterns, however, were not suitable for detailed structural analysis, and single crystals of the hexafluorides could not be isolated.…”
Section: Introductionmentioning
confidence: 88%
“…These hexafluorides all undergo a solid-state transformation from a low-temperature phase, which is probably orthorhombic, to a hightemperature phase of body-centred cubic symmetry. The transformation temperatures lie between 263.6 K for MoF6 and 275.2 K for PtF6 (Siegel & Northrop, 1966). Because this phase change occurs at 263.6 K for MoF6, the sample had to be cooled below this temperature to study the orthorhombic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Between the melting point (290.6 K) and 263.4 K, MoF6 is body-centred cubic, and below 263-4 K it has an orthorhombic structure of the UF6 type (Hoard & Stroupe, 1958). The hexafluorides of the second and third row transition metals all have a cubic form near room temperature and an orthorhombic form at low temperatures (Siegel & Northrop, 1966 Fluorine-19 magnetic-resonance measurements (Rigny & Virlet, 1969) showed that cubic MoF6 is a plastically crystalline phase with the octahedral MoF6 molecules undergoing rapid rotational and slow translational motions.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds are highly moisture-sensitive and corrosive and must be handled in quartz or Kel-F, while the crystals sublime and recrystallize owing to their high vapour pressure. Siegel & Northrop (1966) were unable to isolate single crystals for X-ray structure determination in the course of their powder studies.…”
Section: Introductionmentioning
confidence: 99%